Phthalonitrile resins and composites : properties and applications - Derradji, Mehdi; Jun, Wang; Wenbin, Liu (PDL handbook series., 2018)
Phthalonitrile Resins and Composites: Properties and Applications summarizes the latest research on these polymers, providing information that enables materials scientists and engineers to deploy these polymers in the real world. The book gives details on synthesis and preparation techniques for key phthalonitrile monomers. All curing techniques are discussed, along with blends and copolymers of phthalonitrile with other polymeric materials, such as epoxy, benzoxazine and bismaleimide. Fiber and particle based phthalonitrile micro and nanocomposites are also discussed, along with their potential applications in lightweight automobiles, ships, oil rigs, aircraft, wind blades, high temperature bearings, valves, battery and electronic casings, fire resistant textiles, and more.